The effect of cooling rate on solidification characteristics and grain structure of Al-9Si cast alloy - Ma, Xian Hui; Nur Azhani, Abd Razak; Asnul Hadi, Ahmad; Nasrul Azuan, Alang (Akademi Baru, 2024)
A thermal analysis study is essential before the semisolid metal processing of a particular alloy. The surrounding environment, especially the cooling rate is also an important factor. This study investigated the influence of different cooling rates on thesolidification characteristics and microstructure evolution of the Al-9Si cast alloy. Four cooling mediums were designed, and their cooling rates are 0.16 °C/s, 1.0 °C/s, 1.3 °C/s, and 1.9 °C/s, respectively. The results show that the primary dendrite size ofthe Al-9Si alloy was reduced from 162.61 μm to 86.86 μm as the cooling rate increased from 0.16 °C/s to 1.9 °C/s. Significant grain refinement was observed, however, the external cooling has a negligible impact on solid fraction. The optimal temperature range of the Al-9Si cast alloy for the semisolid metal processing at a solid fraction of 0.5 to 0.7 is between 554 °Cand 563 °C. With these thermal profiles provided, the relationship between the solid fraction and the solidification time could be expressed using the polynomial equation, which is also useful for point prediction in the subsequent semisolid metal processing.